2015
DOI: 10.1021/acs.jnatprod.5b00258
|View full text |Cite
|
Sign up to set email alerts
|

Bisleuconothine A Induces Autophagosome Formation by Interfering with AKT-mTOR Signaling Pathway

Abstract: We have previously reported that bisleuconothine A (Bis-A), a novel bisindole alkaloid isolated from Leuconotis griffithii, showed cytostatic activity in several cell lines. In this report, the mechanism of Bis-A-induced cytostatic activity was investigated in detail using A549 cells. Bis-A did not cause apoptosis, as indicated by analysis of annexin V and propidium iodide staining. Expression of all tested apoptosis-related proteins was also unaffected by Bis-A treatment. Bis-A was found to increase LC3 lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…5 ). PRAS40 is a metabolism protein bound to mTOR complex, and acts as the receptor of mTOR, PRAS40 also can regulate the proliferation in various cell lines ( 12 , 13 ). The results of this work indicated that PRAS40 can be regulated by LicA-induced-ROS in HCCs, and when HCCs were cotreated with LicA and NAC, the change of PRAS40 expression level was inhibited ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). PRAS40 is a metabolism protein bound to mTOR complex, and acts as the receptor of mTOR, PRAS40 also can regulate the proliferation in various cell lines ( 12 , 13 ). The results of this work indicated that PRAS40 can be regulated by LicA-induced-ROS in HCCs, and when HCCs were cotreated with LicA and NAC, the change of PRAS40 expression level was inhibited ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, some of the bisindole alkaloids showed cytotoxicity rather than those with monomeric units [2][3][4]. Various indole alkaloids that exhibited diverse molecular skeleton and significant diverse bioactivity have been reported from our laboratory [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…Bisindole alkaloids possess antibacterial, anti-inflammatory, antimalarial and anticancer properties [7]. Bisleuconothine A modulates the AKT-mTOR signaling pathway and induces autophagosomes [8]. The present investigation was carried out to study the effects of bisleuconothine A and hyperbaric oxygen on traumatic neuronal injury in rats.…”
Section: Introductionmentioning
confidence: 99%